2016
DOI: 10.1080/02640414.2016.1140906
|View full text |Cite
|
Sign up to set email alerts
|

Effects on muscle strength, maximal jump height, flexibility and postural sway after soccer and Zumba exercise among female hospital employees: a 9-month randomised controlled trial

Abstract: This 9-month randomised controlled workplace physical activity trial investigated the effects of soccer and Zumba exercise, respectively, on muscle strength, maximal jump height, sit-and-reach flexibility and postural sway among female workers. A total of 107 female hospital employees aged 25-63 were cluster-randomised to a soccer group, a Zumba group or a control group. Training was conducted outside working hours as two to three 1-h weekly sessions the first 3 months and once a week the last 6 months. Tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Body fat content was reduced in IG only, in line with several other studies using dance as an exercise training intervention [37, 41, 44], but in disagreement with others [45, 47]. In contrast, lean body mass was elevated after intervention in both IG (0.7 kg) and CG (0.4 kg).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Body fat content was reduced in IG only, in line with several other studies using dance as an exercise training intervention [37, 41, 44], but in disagreement with others [45, 47]. In contrast, lean body mass was elevated after intervention in both IG (0.7 kg) and CG (0.4 kg).…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the unorthodox locomotion pattern may be beneficial in terms of improving postural balance. In comparison, several studies on elderly participants using recreational football training and walking football, which also has an unorthodox locomotion pattern, as intervention method, have demonstrated that components of postural balance are markedly improved after periods lasting 12-16 weeks [37, 38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All eligible studies were controlled trials, published in English from the beginning of 2009 until February 2017. In order to perform meta-analysis from 31 papers that met the inclusion criteria, 17 studies5 8 9 23–36 featured data changes in blood pressure, 15 covered RHR,5 8 9 23–25 29–35 37 19 papers2 5 9–11 24–32 34–39 related to body composition, while 10 studies2 11 12 24 38–43 provided sufficient data for muscular fitness. Metabolic responses data extraction featured 10 studies for plasma LDL and HDL,5 9 10 24–26 30 31 35 45 8 studies for plasma triglycerides,9 10 24–26 30 35 45 9 for total cholesterol5 9 10 24–26 30 35 45 and fasting blood glucose,10 24–26 30 31 35 37 45 and 5 for glucose tolerance10 12 24 30 31 35 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This is especially so considering that Zumba has not been effective in improving lower body muscular strength in healthy populations (Barene et al . ). During the investigation, it was observed that the activities organised by the day‐care centre, which were included in the daily routine of the people with ID, were mainly sedentary.…”
Section: Discussionmentioning
confidence: 97%